Natalizumab treatment reduces microglial activation in the white matter of the MS brain - Sucksdorff M; Tuisku J; Matilainen M; Vuorimaa A; Smith S; Keitila J; Rokka J; Parkkola R; Nylund M; Rinne J; Rissanen E; Airas L (LIPPINCOTT WILLIAMS & WILKINS, 2025)
ObjectiveTo evaluate whether natalizumab treatment reduces microglial activation in MS.MethodsWe measured microglial activation using the 18-kDa translocator protein (TSPO)-binding radioligand [C-11] PK11195 and PET imaging in 10 patients with MS before and after 1 year treatment with natalizumab. Microglial activation was evaluated as the distribution volume ratio (DVR) of the specifically bound radioligand in brain white and gray matter regions of interest. MRI and disability measurements were performed for comparison. Evaluation was performed identically with 11 age-and sex-matched patients with MS who had no MS therapy.ResultsNatalizumab treatment reduced microglial activation in the normal-appearing white matter (NAWM; baseline DVR vs DVR after 1 year of treatment 1.25 vs 1.22, p = 0.014, Wilcoxon) and at the rim of chronic lesions (baseline DVR vs DVR after 1 year of treatment 1.24 vs 1.18, p = 0.014). In patients with MS with no treatment, there was an increase in microglial activation at the rim of chronic lesions (1.23 vs 1.27, p = 0.045). No alteration was observed in microglial activation in gray matter areas. In the untreated patient group, higher microglial activation at baseline was associated with more rapid disability progression during an average of 4 years of follow-up.ConclusionsTSPO-PET imaging can be used as a tool to assess longitudinal changes in microglial activation in the NAWM and in the perilesional areas in the MS brain in vivo. Natalizumab treatment reduces the diffuse compartmentalized CNS inflammation related to brain resident innate immune cells.